Effects of Barley Flour and Barley Protein Isolate Addition on Rheological and Sensory Properties of Pita Bread. Issue 5 (4th September 2014) - Alu'datt, Muhammad H.; Rababah, Taha; Al‐Rabadi, Ghaid J.; Ereifej, Khalil; Gammoh, Sana; Masadeh, Nather; Torley, Peter J.
Abstract This study was conducted to evaluate the effect of wheat flour containing various levels (0, 5, 10 and 15%) of barley protein isolate (BPI) and barley flour (BF) on sensory (trained panel and consumer panel) and instrumental (texture and color) properties of Pita bread. Increasing the level of BF or BPI in the flour significantly reduced the aromatic flavor attributes of bread. Results demonstrated that the bread made with increasing ratio of fortification of BF in wheat flour reduced the texture attributes, whereas bread made from increasing the ratio of fortification of BPI had a harder texture. Most of the instrumental, descriptive and consumer results showed that the fortification of 5 and 10% BF were similar to control, and acceptable to the panel and consumers. Practical Applications Results indicated that bread made from fortification of wheat flour with 5 and 10% of BF and BPI showed superior physicochemical and sensory properties compared with the control and 15% and suggested to use it in the food industry with consumer demand acceptability.